(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Earlobe repair is one of the commonest procedures done by plastic surgeons. It is often done for enlarged holes in ear lobules. Bleeding is very common in this procedure which interferes with proper visualization of operative field. Aim of our study was to know the efficacy of SAURABH GUPTA’S TECHNIQUE OF BLOODLESS EAR LOBE REPAIR©, which is done using bull dog clamps. Materials and Methods: This was a prospective study done on 50 ear lobes repaired with the above-mentioned technique over a period of one year at a tertiary care hospital of North India. Demographic and clinical data of the patients were recorded. Also, parameters like visibility of operative field, time taken for surgery, postoperative results at three visits done at 3 days, 1week and 1 month were studied. Results: In our study, bilateral ear lobe tear repair was done in 92.31 % cases, and majority were partial thickness tears. The operative field was found to be clear in 96 % cases with slight ooze not compromising visibility in 4% cases. Mean time taken for surgery on each side was 7.06 ± 0.61 minutes. Postoperatively, 2 patients developed localized edema, which subsided at follow-up visit done at 1 week. No postoperative complications were recorded in rest of the patients. The mean satisfaction score of patients on Likert scale was 4.64 ± 0.48. Conclusions: In our study we found that the SAURABH GUPTA’S TECHNIQUE OF BLOODLESS EAR LOBE REPAIR© is a safe and effective procedure of ear lobe repair. It helps to achieve good hemostasis, providing good operative field, thereby reducing surgical time. The post operative outcomes in all the cases were found to be satisfactory and the level of patient satisfaction was also high.